Two new acridone alkaloids from Glycosmis macrantha - Yahayu, Maizatul Akmal; Rahmani, Mawardi; Mohd Hashim, Najihah; Mohd Amin, Muhammad Aizat; Ee, Gwendoline Cheng Lian; Sukari, Mohd Aspollah; Md Akim, Abdah (MDPI, 2011)
Extraction and chromatographic separation of the extracts of dried stem barks of Glycosmis macrantha lead to isolation of two new acridone alkaloids, macranthanine and 7-hydroxynoracronycine, and a known acridone, atalaphyllidine. The structures of these alkaloids were determined by detailed spectral analysis and also by comparison with reported data.